2019
DOI: 10.3389/fphys.2019.00947
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neuromuscular Training on Agility Performance in Elite Soccer Players

Abstract: Background Agility in general and change-of-direction speed (CoD) in particular represent important performance determinants in elite soccer. Objectives The objectives of this study were to determine the effects of a 6-week neuromuscular training program on agility performance, and to determine differences in movement times between the slower and faster turning directions in elite soccer players. Materials and Methods Twenty male elite soccer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 29 publications
4
38
0
1
Order By: Relevance
“…This multidirectional coordination training may play an important role in improving agility, since some of the main skills involved in coordination and agility are the same. In fact, in concordance with our results, a study conducted on 20 elite U18 soccer players showed improved agility performance after a 6-week multidirectional-based training intervention [ 24 ]. Interestingly, another study that used a coordination training intervention with competition (e.g., using pairs) and without competition (e.g., individually), but using the same drills, found that coordination training with competition produced greater adaptations in agility after eight weeks [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This multidirectional coordination training may play an important role in improving agility, since some of the main skills involved in coordination and agility are the same. In fact, in concordance with our results, a study conducted on 20 elite U18 soccer players showed improved agility performance after a 6-week multidirectional-based training intervention [ 24 ]. Interestingly, another study that used a coordination training intervention with competition (e.g., using pairs) and without competition (e.g., individually), but using the same drills, found that coordination training with competition produced greater adaptations in agility after eight weeks [ 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have shown that coordination is directly related to strength, agility and speed [ 22 , 23 ]. Thus, this type of intervention may be related to potential improvements in agility performance, compared to a control group without such an intervention [ 24 , 25 ]. The main hypotheses of the current study were that a combined coordination and agility training program would enhance (i) agility performance, (ii) power, and (iii) linear sprint.…”
Section: Introductionmentioning
confidence: 99%
“…As a non-traditional form of training, neuromuscular training (NMT) is receiving increasing research attention in the sports field, mainly because NMT is purported to be effective for the rehabilitation of sports injuries ( Zech et al, 2009a ) and prevention of lower limb injuries ( Hübscher et al, 2010 ), through its unique capacity of provoking physiological sensory feedback alterations and therefore enhance joint functionalities ( Hewett et al, 1999 ; Coughlan and Caulfield, 2007 ; Zech et al, 2009b ; Myer et al, 2013 ). The effects of NMT on improving sport performance had also been examined in various physical fitness components, including jumping ( Chappell and Limpisvasti, 2008 ), agility ( Zouhal et al, 2019 ), abdominal endurance ( Barber-Westin et al, 2015 ), and postural control performance ( Paterno et al, 2004 ; Filipa et al, 2010 ; Asadi et al, 2015 ; Benis et al, 2016 ; Zemková and Hamar, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the basic characteristics of the 16 studies included in the review. 9,10,12,13,21,22–32 All of these studies are randomized controlled trials. The sample size ranges from 20 to 122, with a mean of 23 participants.…”
Section: Resultsmentioning
confidence: 99%